Complex Aesthetic Treatment of Patients with Multiple Caries - Devi Eka Juniarti; Tamara Yuanita; Nirawati Pribadi; Tarsardo Marbun; Nadien Sekar Pramesti (Conservative Dentistry Journal, 2022)
Background: The need for dental esthetics is very important in recent years. Fulfilling aesthetic demands with both non-invasive and minimally invasive techniques can maintain tissue continuity. A 38 year old female patient came to the clinic with an esthetic complaint of maxillary anterior teeth. The following case report describes a step by step complex aesthetic treatment of a patient with multiple caries. Appealing aesthetic results will restore the patient's smile through restorative treatment in dentistry. Purpose: The purpose of this case report is to explain the management of complex aesthetic treatment of patients with multiple caries Case: A 38-year-old female patient complained her upper front teeth is turning black. The patient complained that her teeth had hurt ± 3 months ago and sometimes felt sore. The patient wants her teeth to be treated because she feels less confident when she smiles and wants to fix these teeth. The history of treatment on the tooth in question have had root canal treatment and been filled since 8 years ago. The tooth has had braces (orthodontic) treatment and was removed ± 7 years ago. The patient stated that she had no systemic health disorder. Case management : The treatment of this complex case were done using root canal treatment, endodontic retreatment, direct and indirect veneer, dowel, and crown. Conclusion: complex aesthetic treatment of patients with multiple were done aiming for good aesthetic result